Enhanced photodegradation of phenol by ZnO nanoparticles synthesized through sol-gel method - Nikathirah Yusoff,; Ho, Li-Ngee; Ong, Soon-An; Wong, Yee-Shian; Wanfadhilah Khalik,; Muhammad Fahmi Ridzwan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Zinc oxide (ZnO) utilization in advanced oxidation process (AOP) via solar-photocatalytic process was a promising method for alternative treating wastewater containing phenol. The ZnO photocatalyst semiconductor was synthesized by sol-gel method. The morphology of the ZnO nanostructures was observed by using scanning electron microscope (SEM) and the crystallite phase of the ZnO was confirmed by x-ray diffraction (XRD). The objective of this study was to synthesis ZnO nanoparticles through a sol-gel method for application as a photocatalyst in the photodegradation of phenol under solar light irradiation. The photodegradation rate of phenol increased with the increasing of ZnO loading from 0.2 until 1.0 g. Only 2 h were required for synthesized ZnO to fully degrade the phenol. The synthesized ZnO are capable to totally degrade high initial concentration up until 45 mg L-1 within 6 h of reaction time. The photodegradation of phenol by ZnO are most favoured under the acidic condition (pH3) where the 100% removal achieved after 2 h of reaction. The mineralization of phenol was monitored through chemical oxygen demand (COD) reduction and 92.6% or removal was achieved. This study distinctly utilized natural sunlight as the sole sources of irradiation which safe, inexpensive; to initiate the photocatalyst for degradation of phenol.